Management, risk factors and treatment outcomes of rhegmatogenous retinal detachment associated with giant retinal tears: scoping review - Miguel A. Quiroz-Reyes; Zaheer-Ud-Din Babar; Rabia Hussain; Zhe Chi Loh; Erick A. Quiroz-Gonzalez; Miguel A. Quiroz-Gonzalez; Virgilio Lima-Gomez (International Journal of Retina and Vitreous, 2024)
Abstract Background Rhegmatogenous retinal detachment (RRD) is a serious condition that occurs when the retina detaches from its underlying retinal pigment epithelium. RRDs associated with giant retinal tears (GRTs) are caused by retinal tears at least 90° or one-quarter of the circumferential extent. This scoping review systematically identifies and summarizes clinical studies evaluating surgical techniques for the management of GRT-related RRDs, discusses functional and visual outcomes and the risk factors affecting treatment outcomes. Methods This study was conducted in accordance with the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. PubMed, Scopus, Google Scholar, and Springer Link databases were searched for relevant papers (from January 2001 to March 2023). Studies that were published in the English language and reported the risk factors, management, and treatment outcomes of GRT-related RRDs were included in the review. The outcome measures included anatomic success rates, changes in BCVA (logMAR) from baseline to the final follow-up, and adverse events. Results A total of 11,982 articles were identified. After the title and abstract review, 71 studies were deemed eligible for full-text review. Thirty-six studies that met the eligibility criteria were included in the final review. Four surgical techniques were identified: pars plana vitrectomy (PPV), combined PPV and scleral buckling, scleral buckling alone, and pneumatic retinopexy. Various types of tamponades, including gas, silicone oil, and air, have been used. PPV was the most commonly used surgical technique in 33.1–100% of patients. Among the 20 studies that used PPV alone, 17 were associated with preoperative PVR. In addition, scleral buckling alone or in combination with PPV was reported as a treatment option in 10 studies, with 2–100% of patients experiencing scleral buckling alone and 13.6–100% experiencing combined PPV and complementary scleral buckling. Primary anatomic success (PAS) was achieved with retinal reattachment via a single operation with no residual tamponade, whereas final anatomic success (FAS) was achieved via more than one operation with no residual tamponade. Reported single surgery anatomic success (SSAS) rates range from 65.51 to 100%. The preoperative best-corrected visual acuity (BCVA) ranged from 0.067 to 2.47 logMAR, whereas the postoperative BCVA ranged from 0.08 to 2.3 logMAR. An improvement in visual acuity was observed in 29 studies. Cataracts (3.9-28.3%) were the most common postoperative complication, followed by high IOP (0.01-51.2%) and PVR (0.8-31.57%). Conclusion PPV is the most common surgical technique, and currently microincision vitrectomy surgery (MIVS) systems are commonly employed. Silicone oil is the most frequently used tamponade in RRD repair. Risk factors for GRT-related RRD include age, sex, lens status, high myopia status, proliferative vitreoretinopathy (PVR), presenting visual acuity, the extent of the GRT and retinal detachment, and macular involvement. Future research areas include guidelines to reduce variability in the reporting of surgical methodology, choice of tamponades, and reporting of functional and visual outcomes to inform the best therapeutic interventions in GRT-related RRD.